Sindroma Lisis Tumor pada Leukemia Limfoblastik Akut L2 - Hari Oki, Hambiah; Dian Sukma Hanggara; Hani Susianti; Nugroho, Susanto (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Background: Tumor lysis syndrome is metabolic abnormalities due to accumulation of intracellular contents in systemic circulation. Cairo and Bishop criteria is used to diagnosing it. Patient with hematological malignancies such as acute leukemia is more prone to this syndrome, and also infection that comes with it. Evaluating tumor lysis syndrome, especially knowing which laboratory parameters used and probable complication are crucial. Case Report: Two years old boy undergone maintenance chemotherapy for his ALL L2 that has been diagnosed one year ago. Patient has no complaint at admission, but went to worsened condition as the chemotherapy was given. Electrolyte imbalances and clinical manifestations depicting tumor lysis syndrome was found. Patient also experiencing pneumonia, gastrointestinal tract infection and sepsis (PELOD score 15). Conclusion and Suggestion: Patient experiencing tumor lysis syndrome when he was going through maintenance chemotherapy. Even though he was admitted without any major complaints, but hyperuricemia and elevated creatinine at the time of admission should be considered before initiating chemotherapy. Sepsis in this patient might be cause by bacterial infection of the gastrointestinal tract due to his severe neutropenia condition.